Nutrient management through organic amendments to ensure sustainable and economic cultivation of radish - Suman, Shekhar; Singh, Shailesh Kumar; Bhati, Dashrath (Plant Science Today, 2024)
Radish cultivation heavily relies on fertilizers, adversely affecting soil health. Shifting to organic practices is crucial for sustainability. This study explores combinations of organic amendments (farmyard manure, vermicompost, and poultry manure) to enhance radish growth and yield economically. Ten treatments were tested using a Randomized Block Design. One-way ANOVA, correlation, and regression analyses were conducted. The combination of 50% vermicompost and 50% poultry manure yielded the best results in plant height, leaf growth, fresh and dry weights, and root size. The highest yield (280 q/ha) was achieved with this combination, followed closely by 75% vermicompost and 25% poultry manure (245 q/ha), and 50% farmyard manure with 50% poultry manure (228 q/ha). This combination also proved the most economically and environmentally sustainable, with a benefit-cost ratio of 2.48. Compared to the control, it delivered a gross return 2.44 times higher and a net return 2.85 times higher. Incorporating poultry manure and vermicompost as nutrient sources in radish cultivation is a scientifically sound and economically viable approach, contributing to sustainable agriculture and aligning with UN Sustainable Development Goals.